1997
DOI: 10.1103/physrevd.56.6391
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational excitons from extra dimensions

Abstract: Inhomogeneous multidimensional cosmological models with a higher dimensional space-time manifoldMi (n ≥ 1) are investigated under dimensional reduction to D0 -dimensional effective models. In the Einstein conformal frame, small excitations of the scale factors of the internal spaces near

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(176 citation statements)
references
References 47 publications
8
167
1
Order By: Relevance
“…It then follows from the field equations that the SET components, and hence the quantities V and ( ϕ) 2 , decay at large ρ ≈ r quicker than r −(d0+1) . Let us now prove the following no-hair theorem, extending to our system the theorems known in four dimensions [3,4]: (20) for D ≥ 4 , with a positive-definite matrix H KL ( ϕ) and V ( ϕ) ≥ 0 , the only asymptotically flat black hole solution is characterized by V ≡ 0 , ϕ = const and the Tangherlini metric (22), (25) in the whole range h < ρ < ∞ where ρ = h is the event horizon.…”
Section: No-hair Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…It then follows from the field equations that the SET components, and hence the quantities V and ( ϕ) 2 , decay at large ρ ≈ r quicker than r −(d0+1) . Let us now prove the following no-hair theorem, extending to our system the theorems known in four dimensions [3,4]: (20) for D ≥ 4 , with a positive-definite matrix H KL ( ϕ) and V ( ϕ) ≥ 0 , the only asymptotically flat black hole solution is characterized by V ≡ 0 , ϕ = const and the Tangherlini metric (22), (25) in the whole range h < ρ < ∞ where ρ = h is the event horizon.…”
Section: No-hair Theoremmentioning
confidence: 99%
“…The coefficient of m is chosen in (25) and accordingly in (23) in such a way that at large r in case Λ = 0 , when the space-time is asymptotically flat, a test particle at rest experiences a Newtonian acceleration equal to −GM/r d 0 .…”
Section: No-hair Theoremmentioning
confidence: 99%
“…We investigated stability of some of these models under the conformal excitations which are functions of 4-D space-time. Such excitations are of special interest because they behave as massive minimal scalar fields in 4-D space-time, for example can be observed as massive scalar particles -gravitational excitons on branes, as it takes place in the Kaluza-Klein approach [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…To be in agreement with observations, internal spaces should be compact, static (or nearly static) and less or order of electro-weak scale (the Fermi length). The stability problem of these models with respect to conformal perturbations of the internal spaces was considered in detail in our paper [1]. It was shown that stability can be achieved with the help of an effective potential of a dimensionally reduced effective 4-D theory.…”
Section: Introductionmentioning
confidence: 99%
“…These internal space scalefactor small fluctuations/oscillations have the form of a scalar field (so called gravexciton [20]) with a mass m ψ defined by the curvature of the effective potential (see for detail [20]). Action (2) is defined under the approximation κ 0 ψ < 1 that obviously holds for the…”
mentioning
confidence: 99%